Posteromedial Hypothalamic Deep Brain Stimulation for Refractory Aggressiveness in a Patient With Weaver Syndrome: Clinical, Technical Report and Operative Video. Issue 3 (20th May 2021) - Blasco García de Andoain, Guillermo; Navas García, Marta; González Aduna, Óscar; Bocos Portillo, Alvaro; Ezquiaga Terrazas, Elena; Ayuso-Mateos, José Luis; Pastor, Jesús; Vega-Zelaya, Lorena; Torres, Cristina V
Abstract: BACKGROUND AND IMPORTANCE: Deep brain stimulation of the posteromedial hypothalamus (PMH DBS) appears to be an effective treatment for drug-resistant aggressiveness. Weaver syndrome (WS) is a rare genetic disorder in which patients develop some degree of intellectual disability and rarely severe behavioral alterations that may benefit from this procedure. CLINICAL PRESENTATION: We present the case of a 26-yr-old man diagnosed with WS presenting with uncontrollable self and heteroaggressiveness and disruptive behavior refractory to pharmacological treatment and under severe physical and mechanical restraining measures. The patient was successfully treated with bilateral PMH DBS resulting in affective improvement, greater tolerance for signs of affection, regularization in his sleep pattern and appetite disturbances at 12-mo follow-up. A detailed description and video of the procedure are presented, and a review of the clinical characteristics of WS and the utility and benefits of PMH DBS for refractory aggressiveness are reviewed. CONCLUSION: To our knowledge, this is the first case of refractory aggressiveness described in WS as well as the first patient with WS successfully treated with PMH DBS.